PENGARUH PENGGUNAAN SERAT HIGH DENSITY POLYETHYLENE (HDPE) PADA CAMPURAN BETON TERHADAP KUAT TARIK BETON - Erwin Rommel; Yunan Rusdianto; Anita Kurniati (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2014)
PENGARUH PENGGUNAAN SERAT HIGH DENSITYPOLYETHYLENE (HDPE) PADA CAMPURAN BETON TERHADAPKUAT TARIK BETON1)Erwin Rommel, 2)Yunan Rusdianto, 3)Anita Kurniati1,2,3)Jurusan Teknik Sipil Fakultas Teknik Universitas Muhammadiyah Malang3)Alumni Teknik Sipil FT-UMMemail : erwin67pro@yahoo.comABSTRACTResearch on the addition of HDPE fibers in normal concrete is intended to determine therelationship between the percentage of variation of fiber addition of HDPE to the workability, tensilestrength and determine the pattern of deployment of fiber in concrete. The addition of HDPE fibersis intended to increase the tensile strength of concrete.The concrete was mixed using gresik cement type PPC, sand with the gradation limits zone 2,the gravel with a maximum grain size of 20 mm, and HDPE fibers with a width of 0.5 cm and 2.5cm long. Variations in the addition of HDPE fibers are 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%,9%, 10% of the volume of the mixture. Tensile strength testing performed with a cylindrical testpiece with a diameter of 150 mm and 300 mm height at the age of 28 days of the test object. Tensilestrength of concrete data analysis using regression analysis.The results showed that the addition of HDPE fibers can increase the value of tensile strengthsides. There is a strong pull on the sides of the optimum levels of 4% with a tensile strength of 2.86MPa increased by 18%Key words: Concrete, HDPE fibers, Tensile strength